The InfraJoint Protocol for Infrared Thermography of the Hands and Wrists in the Assessment of Inflammatory Arthropathies - Poubel, Rodrigo; Oliveira, Luiz Eduardo; Gáudio, Rodrigo; Pastura, Flávia; Sampaio, Ronald; Machado, Ladan; Murta, Leonardo; Braganholo, Vanessa; Conci, Aura (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
The diagnostic differentiation between inflammatory arthropathies and non-inflammatory musculoskeletal disorders is challenging in primary care and in resource-constrained settings, where access to ultrasonography with power Doppler, computed tomography, or magnetic resonance imaging is limited. Infrared thermography of the hands and wrists is a promising low-cost, contactless and ionizing-radiation-free modality to support this triage, but its broader clinical adoption is held back by the absence of standardized acquisition protocols. In this paper we contribute (i) the InfraJoint acquisition protocol, which combines a static phase and a dynamic cooling/rewarming phase over a controlled support, and (ii) preliminary results from an ongoing cohort of patients with rheumatoid arthritis and healthy controls, characterizing the clinical profile of the recruited population and the pattern of joint involvement.